EMPLOYING BUZZ MARKETING AS ONE OF PROMOTION TOOLS TO DEAL WITH DYNAMIC PURCHASING BEHAVIOUR OF SMARTPHONES - Ahmed Ghaffar Hussein; Saif Ali Jasim (Journals Park Publishing, 2023)
The study seeks to determine how buzz marketing can be used as one of the promotional tools for dealing with dynamic purchasing behavior. Based on the previous claim, the current study aimed to measure the impact of buzz marketing as one of the promotion tools in the dynamic purchasing behavior of customers towards salespeople and invest it in a way that enhances the value of the thoughtful sample. In order to collect data, sales representatives were surveyed by a group of mobile phone companies, distributing (175) a survey form to salespeople. After retrieving the forms, it was found that the forms valid for analysis represented reality (157) and indicated a response ratio of 93.7%. In order to achieve the study's objective, a range of methods have been used to test the applied aspects of the study. Perhaps the most famous of these methods represents the average computational, standard deviation, and level of importance, Pearson's correlation coefficient (SPSS.V.27), and influence factors between internal variables according to the program (AMOS.V.26). The results showed a moral correlation between buzzing marketing as one of the promotion tools and dynamic purchasing behavior, as well as an impact relationship between buzzing marketing as one of the promotion tools and dynamic buying behavior, to show the interest of the specimen in dealing with its different capabilities.
Keywords: buzzing marketing, dynamic purchasing behavior.